“If we don’t adapt, we lose some parents”. Collaborations with migrant families in the context of student wellbeing - Szelei, Nikolett; Langer Primdahl, Nina; Skovdal, Morten; Aalto, Sanni; Osman, Fatumo; Hilden, Per Kristian; Kankaanpää, Reeta; Andersen, Arnfinn J.; Sarkadi, Anna; Watters, Charles; Derluyn, Ilse (Taylor & Francis, 2026)
Based on focus group discussions with secondary school teachers in Denmark, Finland, and Sweden, we investigated teachers’ views on home-school collaborations with migrant families in the context of student wellbeing. We asked 1) what roles and strategies constituted home-school collaborations in teachers’ views, 2) what norms of belonging characterized teachers’ perceptions on collaborations; and, 3) to what extent teachers’ perceptions of home-school collaborations reflected equity. The findings revealed two major themes: seeing parents in paradoxical roles and attempting to collaborate in a context of constraints. These themes were often underpinned by teachers’ perceived ‘ideals’ on the educational, cultural-linguistic, familial and psychosocial characteristics of a ‘family’ and a ‘parent’. These assemblages seemed to set belonging for migrant families on condition of meeting teacher-perceived ideals, and pointed to the necessity to enable plural belonging to a collaborative school community that fosters wellbeing.